Analisis dan Komparasi Luaran Publikasi Ilmiah Sejumlah Perguruan Tinggi Muhammadiyah - Milana Abdillah Subarkah; Anuraga Jayanegara (Jurnal Pendidikan Islam, 2021)
This study aimed to analyze and to compare the output of scientific publications, both national and international, from a number of Muhammadiyah universities. The source of data used in this study was originated from the Science and Technology Index (SINTA) portal, and as many as 35 Muhammadiyah universities were the objects of this study. Data were analyzed using a correlation analysis and a multivariate analysis, namely principal component analysis (PCA). Results showed that the variables of Scopusindexed publication, SINTA-indexed publication, SINTA score, number of academic staffs, and the ratio between Scopus-indexed publication to the number of academic staffs had positive and significant correlations (P<0.001). The PCA results indicated that several universities, namely UM Surakarta, Ahmad Dahlan University and UM Yogyakarta were in a separate cluster from other Muhammadiyah universities, i.e., the superior cluster in terms of publication output. Other universities that close to themwere UM Malang and UHAMKA.